The impact of demographic profile on emotional intelligence among the faculty members performance in the educational institutions in Tamil Nadu, India - an empirical study. (2016) - Vasumathi, A.; Sagaya, Mary T.; Subashini, R.
An individual's satisfaction, performance and success at work and family life are varying with the respondents' different demographic profiles which were influenced on emotional intelligence. The competitive reality in the present scenario poses a great challenge on being excellent performers. Excellent performance is mandatory for the educational institutions particularly for the private educational institutions faculty members would face pressure from different people such as management, parents of the students, students and from one's own family. In this regard, the researchers have selected three private educational institutions for the study for finding out the impact of demographic profile on emotional intelligence among faculty members' performance in Tamil Nadu. From the study, it is proved that socio-demography do affect the emotional intelligence among faculty members work performance. This study also proved that the aged faculty members' EI was high when compared to young aged faculty members.